A Rationable for Early Intervention - Nur Azizah (JPK (Jurnal Pendidikan Khusus), 2009)
Young children with special needs are not automatically posses one or more those skills and as consequence, teachers in early intervention purposely have to teach those skills directly. It is essential for young children with special needs to commence in early intervention, because at this age, which is belived as a golden age, is a strategic time to shape young children with special needs by age-appropriate skills. The implementation of early intervention builds from at least four components which are: Firstly, theoretical base about learning and development. Secondly, empirical research where many studies show that early intervention give advantages for young children with disabilities and their parents and communities. Thirdly, expert opinions which draw from theoretical and empirical research and lastly changing in society concerning values and attitude towards people with disabilities. There are five theoretical model of curriculum in early intervention, namely: Developmental Curriculum Model, Developmental-Cognitive Curriculum Model, Academic (or pre-academic) Skills Model, Behavioral Curriculum Model, and Functional Curriculum Model.